The Virtual Bingo Blower: An open-source tool to generate ambiguity and risk in experiments - Ola Andersson; Geoffrey Castillo; Erik Wengström (Lund University, School of Economics and Management, Department of Economics, 2024)
We propose the Virtual Bingo Blower (VBB) as a way to generate credible risk and ambiguity in computerized experiments. Using a physics engine-a computer simulation of a physical system-the VBB simulates a conventional bingo blower. Different aspects of the VBB, such as the number of balls, their color, and their speed, can be easily modified. In an online experiment, we measure ambiguity attitudes and vary the source of ambiguity, using either the VBB or natural events. We find that the VBB and natural events result in a similar degree of ambiguity aversion. Further, we find that, by manipulating the number of balls, the VBB can be used to manipulate the perceived level of ambiguity
Keywords: C91; D81; 330; ambiguity; risk; bingo blower; online experiment; experimental tools; randomization